Advancing Cloud Adoption in the Saudi Public Sector: Challenges, Global Insights, and Strategic Policy Recommendations - Abdal Hafeth Alaraj (European Scientific Journal, ESJ, 2025)
Cloud computing has become a cornerstone of digital transformation strategies in the public sector, offering government entities scalable infrastructure, cost efficiency, and enhanced service delivery. In Saudi Arabia, adopting cloud technologies is a national priority aligned with Vision 2030, aiming to modernize government operations and increase digital agility. However, the transition to cloud environments within government institutions faces several challenges. This paper explores the key barriers to cloud computing adoption in Saudi Arabia's governmental sector. These include data governance concerns, cybersecurity requirements, organizational readiness gaps, and rigid procurement models. Through a comprehensive analysis of national frameworks and sector-specific studies, the paper uncovers the root causes of slow adoption and identifies opportunities for improvement. The study also draws comparative insights from global practices, offering lessons that can inform local strategies. Based on the findings, it proposes practical recommendations to support more effective cloud adoption in the Kingdom's public sector. These focus on governance enhancement, capacity building, policy alignment, and fostering a cloud-positive culture within institutions.